The Influence of Visual Learning Styles on Learning Outcomes in PAUD Tegar Tangguh Kampung Gunung, Simalungun Regency - Wahyudi, Muhammad; Ridwan, Rahmad (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to determine the effect of visual learning style on visual learning style on early childhood learning outcomes at PAUD Tegar Tangguh hamlet II village Bandar Jawa, Bandar Sub-district, Simalungun Regency. this research is motivated by the results of observations conducted and found interesting facts that the majority of learning activities still use auditory learning styles. The results of this observation revealed that learning methods that focus on hearing, such as listening to stories or verbal explanations, are not the main preference for students in absorbing information. The type of research conducted by researchers in this study is quantitative research with multiple linear regression methods. This research was conducted at PAUD Tegar Tangguh hamlet II village Bandar Jawa, Bandar District, Simalungun Regency with a sample of 30 students out of 120 students. Data collection was done by giving a questionnaire with a Likert scale model. Data analysis used is using multiple regression analysis. The results of this study indicate that visual learning styles have an effect on learning outcomes. early childhood, this can be seen from the significance value which is worth (Sig 0.000 <0.05) and for the value of F count> F table (28.830 > 3.34). The coefficient of determination of the effect of visual learning style variables on early childhood learning outcomes is 59.7% while the rest is influenced by other variables